2000
DOI: 10.1523/jneurosci.20-11-04165.2000
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I Stimulates Dendritic Growth in Primary Somatosensory Cortex

Abstract: The temporal and spatial distributions of several growth factors suggest roles in the regulation of neuronal differentiation in the neocortex. Among such growth factors, the insulin-like growth factors (IGF-I and -II) are of particular interest because they are available to neurons from multiple sources under independent control. IGF-I is produced by many neurons throughout the brain and also by cells in the cerebral vasculature. IGF-II is found at high levels in the CSF, and both IGF-I and IGF-II cross the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 68 publications
5
112
3
1
Order By: Relevance
“…2 A). In addition to neuronal activity, several secreted factors, including BDNF and insulin-like growth factor (IGF), are known to promote dendrite growth (4,22). Although insulin can activate GGT in non-neuronal cells (23,24), we found that neither insulin nor IGF-1 had any effect on GGT activity under our experimental conditions (Fig.…”
Section: Activation Of Ggt By Neuronal Activity or Bdnfmentioning
confidence: 68%
“…2 A). In addition to neuronal activity, several secreted factors, including BDNF and insulin-like growth factor (IGF), are known to promote dendrite growth (4,22). Although insulin can activate GGT in non-neuronal cells (23,24), we found that neither insulin nor IGF-1 had any effect on GGT activity under our experimental conditions (Fig.…”
Section: Activation Of Ggt By Neuronal Activity or Bdnfmentioning
confidence: 68%
“…Evidence from animal research, suggests that growth hormone and IGF-I are important in neurodevelopment (20), and may therefore potentially be physiological mediators of the association of short birth length with schizophrenia (21).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…While de novo mutations in paternal germ cells provide a reasonable or at least possible explanation for the paternal age-schizophrenia association, causal pathways explaining associations of size at birth and size in young adulthood with schizophrenia are largely unknown. However, since IGF-I is a major regulator of childhood growth (19) and is also influencing brain development in animal research (20), an intriguing hypothesis for future research is that IGF-I serves as a biological link between childhood growth, body size in adulthood and schizophrenia.…”
Section: Concluding Remarkmentioning
confidence: 99%
“…However, the size and shape of neuritic arbors are influenced by environmental factors. Therefore, we examined whether NHE1 might also influence the effects of three agents that are known to promote neurite elongation and/or branching in mammalian central neurons, i.e., netrin-1 (Barallobre et al, 2005;Round and Stein, 2007), BDNF (Huang and Reichardt, 2001), and IGF-1 (Niblock et al, 2000). These experiments were performed on neocortical neurons obtained from P0.5 NHE1 ϩ/ϩ mice and their NHE1-null mutant (NHE1 Ϫ/Ϫ ) littermates and maintained in primary culture for 72 h.…”
Section: The Role Of Nhe1 In Trophic Factorstimulated Early Neurite Omentioning
confidence: 99%